Effects of Tongxinluo on myocardial fibrosis in diabetic rats. Issue 3 (March 2016) - Wang, Xiaomei; Mu, Changzheng; Mu, Tianchi; Gao, Lili; Zhao, Yaxue; Zhang, Yangyi; Zhang, Zhimian
Abstract : Background : The aim of this study was to explore the effect of Tongxinluo on myocardial fibrosis in diabetic rats and its possible mechanism of action. Methods : Diabetic rat models were established and then divided into three groups: control, diabetes, and Tongxinluo groups. Heart function and myocardial interstitial collagen volume fraction were investigated, and the protein and mRNA expression levels of transforming growth factor beta 1 (TGF‐β1 ), Smad3, and Smad7 were measured. Results : Heart function was clearly abnormal in the diabetes group compared with that in the control group, and the collagen volume fraction and mRNA expression levels of TGF‐β1 and Smad3 were higher. However, the protein and mRNA expression levels of Smad7 were lower. In the Tongxinluo group, it was observed that these indicators were improved. Conclusion : Tongxinluo was effective for the prevention and treatment of myocardial fibrosis in diabetic rats. It probably mediates the expressions of TGF‐β1, Smad3, and Smad7 in rat cardiomyocytes to reduce the occurrence of myocardial fibrosis in diabetic rats.